Understanding the emergence and evolution of new business models in the UK regenerative medicine sector. Issue 3 (4th March 2021) - Banda, Geoffrey; Mittra, James; Tait, Joyce; Watkins, Andrew; Omidvar, Omid
ABSTRACT: This paper identifies, characterises and analyses six evolving regenerative business (RM) models in the UK based on 10 cases we studied. Our conceptual framework extracts four key elements from contemporary business model and value chain literature; architecture/structure, value creation and extraction, networks and linkages, and governance. Using the case study method, we identified the following business models: materials and service provision; early exit: Phase I/II; manufacturing and scale up; translational services; virtual; and integrated. All the business models are still pre-revenue, except for manufacturing and scale up which generates revenue from contract manufacturing therapies for clinical trials. The RM sector is still evolving and consequently the business models are still in flux. Two key challenges for the sector are scalability and sustainability, which creates challenges for pre-emptive policy and practice interventions. We conclude that pre-emptive policy design should support value chain upgrading, paying particular attention to short, medium and long-term sustainability of the RM innovation eco-system, especially evolution of a broad base of SMEs that can take over when public funding is withdrawn. A proportionate and adaptive regulatory environment will be critical to supporting evolving business models even as value chain upgrading occurs.